PERLINDUNGAN HUKUM TERHADAP ASISTEN RUMAH TANGGA DALAM TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA (ANALISIS PUTUSAN NOMOR:791/Pid.B/2015/PN.Mdn) - Johanes M. Aritonang; Triono Eddy (JURNAL DOKTRIN REVIEW, 2022)
Household Assistants are vulnerable to arbitrary actions by their employers, where these arbitrary actions always occur in the house which is a private and personal area or area that cannot be reached by other people, even areas or areas that are very hidden from view. general vision. So to find out the legal protection for ART in domestic violence crimes, it is necessary to research on regulations related to legal protection for ART in domestic violence crimes, and efforts to resolve legal problems against ART in domestic violence crimes, as well as the obstacles faced in efforts to implement protection for ART victims. domestic violence. It is known that the regulation related to legal protection for ART in PKDRT is in Law no. 23 of 2004 concerning (UUPKDRT) Article 2 paragraph (1) letter (c) explains that the scope of the household includes. People who work help the household and stay in the household. People who work as referred to in letter c are considered as family members for the period of time they are in the household in question. And Efforts to resolve legal problems against ART in domestic violence crimes, by carrying out criminal legal efforts, which are the duties and authorities of institutions tasked with enforcing the law, by making complaints to law enforcement, namely the Police